Burg Brink: Bischofshof des 13. Jahrhunderts und spätmittelalterliche Burg. - Atzbach, Rainer; H.W.B. Hansen, Philip; Lundgård Kisum Nielsen, Christine; Lyder Tissot, Victoria (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
The Brink castle site at Ballum-Østerende, Tønder Municipality, is generally characterised by poor preservation conditions. Compared to the early excavations between 1999 and 2002, the investigations between 2017 and 2023 uncovered heavily impacted and ploughed-over contexts. Detector finds and two postholes indicate a settlement here from the Viking Age, particularly in the low-lying nortwestern area which was covered by thick culture layers. These protective fill layers were probably applied until the 13th century, in the lead-up to the construction of a large hall by the bishop of Ribe. The culture layers significantly altered the original topography, a rather pronounced hillside*(Danish »brink«), which gave the castle the name that has been preserved in the adjacent »Brink Møllegård« to this day. The three-zone masonry building was erected on a sand foundation and can be identified as a lordly palatium. In the 14th century, the complex –likely initially only a lightly fortified bishop’s residence – was massively reinforced making it one of the largest castles in Denmark. In its northern outer bailey, the castle’s economic area comprised an intensively used hearth and a brewery. In the mid 16th century, Brink was abandoned. The excavation results show intensive dismantling of the stone buildings, especially of the main castle. The moats were rapidly filled in–and the once magnificent complex went into oblivion.